Evaluating the Feasibility and User-Friendliness of an Augmented Reality–Integrated Physics Textbook on Motion Dynamics - Hasyim, Mutahharah; Haris, Abdul; Taqwin, Muhammad; Ramadhan, Imam; Fatmawaty (Jurnal Pendidikan Fisika, 2026)
Physics learning in the 21st century requires interactive, technology-enhanced instructional resources that support students' understanding of abstract concepts, particularly those related to the dynamics of motion. However, many augmented reality (AR)-based learning tools remain limited to standalone applications and are not adequately integrated into structured instructional materials, which may reduce their pedagogical value and classroom usability. Therefore, this study aimed to develop and evaluate an Augmented Reality Integration (ARI)-based physics textbook designed to improve the feasibility and user-friendliness of AR-supported learning materials in physics education. The study employed a development research approach based on the design thinking model, comprising five stages: empathize, define, ideate, prototype, and test. The ARI textbook was developed by integrating textbook content, student worksheets, and marker-based augmented reality features into a unified learning resource on motion dynamics. Data were collected through literature review, observations, interviews, expert validation, and usability testing involving teachers and students. Feasibility was assessed using Gregory’s expert agreement analysis, while usability and user experience were evaluated using the System Usability Scale (SUS) and the User Experience Questionnaire (UEQ). The results showed that the developed textbook achieved a Gregory coefficient of 1.00 for both content and language, indicating a high level of feasibility for classroom use. The SUS results further indicated that the textbook was acceptable for learning, although differences were found between Grade X and Grade XII students in terms of ease of use and independence. In addition, the UEQ results demonstrated improvements across all users experience dimensions after iterative refinement, particularly in stimulation, attractiveness, and perspicuity. The novelty of this study lies in integrating augmented reality into a structured physics textbook, developed through a user-centered design thinking approach, rather than as a standalone application. In conclusion, the ARI-based textbook is feasible and user-friendly, and it contributes to physics education by providing an innovative, interactive, and pedagogically meaningful learning resource for visualizing abstract concepts.